2011
DOI: 10.1038/emboj.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of UbcH5c and the nucleosome by the Bmi1/Ring1b ubiquitin ligase complex

Abstract: The Polycomb repressive complex 1 (PRC1) mediates gene silencing, in part by monoubiquitination of histone H2A on lysine 119 (uH2A). Bmi1 and Ring1b are critical components of PRC1 that heterodimerize via their N-terminal RING domains to form an active E3 ubiquitin ligase. We have determined the crystal structure of a complex between the Bmi1/Ring1b RING-RING heterodimer and the E2 enzyme UbcH5c and find that UbcH5c interacts with Ring1b only, in a manner fairly typical of E2-E3 interactions. However, we furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
155
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 69 publications
11
155
0
Order By: Relevance
“…Together, the foregoing data show that the hRNF4 RING domain contains a non-specific DNA binding element related to that in the RING1b RING domain [28]. However, we note that DNA binding per se may not be the key function of the hRNF4 basic cluster, as it is structurally related to motifs in the RNF168 and RING1b RING domains that support nucleosome-targeting [4,28].…”
Section: Dna Binding By the Rnf4 Ring Domainmentioning
confidence: 94%
See 3 more Smart Citations
“…Together, the foregoing data show that the hRNF4 RING domain contains a non-specific DNA binding element related to that in the RING1b RING domain [28]. However, we note that DNA binding per se may not be the key function of the hRNF4 basic cluster, as it is structurally related to motifs in the RNF168 and RING1b RING domains that support nucleosome-targeting [4,28].…”
Section: Dna Binding By the Rnf4 Ring Domainmentioning
confidence: 94%
“…However, we note that DNA binding per se may not be the key function of the hRNF4 basic cluster, as it is structurally related to motifs in the RNF168 and RING1b RING domains that support nucleosome-targeting [4,28]. This structural homology has interesting implications for hRNF4 function in the DDR.…”
Section: Dna Binding By the Rnf4 Ring Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, PRC1 poly-ubiquitinates Geminin, a DNA replication inhibitor, to sustain adult hematopoietic stem cell activity (23). Protein structure analysis revealed that within the PRC1 complex, Bmi1 and RNF2 heterodimerize via their N-terminal RING domains to form an active E3 ubiquitin ligase (24)(25)(26). The overexpression of Rnf2 has also been documented in clinical gastrointestinal tumors and lymphomas (27).…”
mentioning
confidence: 99%